Nonbreeding Bird Communities Along an Urban–Rural Gradient of a Tropical City in Central Myanmar. (November 2016) - Suarez-Rubio, Marcela; Aung, Thein; Lin Oo, Sai Sein; Shwe, Nay Myo; Hlaing, Nay Myo; Naing, Kyaw Myo; Oo, Tun; Sein, Mie Mie; Renner, Swen C.
Urbanization is known to be a major driver in abundance and species richness of birds. However, how birds respond to urbanization in tropical cities is understudied in general and entirely absent from Myanmar. We conducted a study in and around Mandalay, a large city in central Myanmar to gather first data on birds and their response to urbanization. We selected four habitats with 10 sampling points each in November 2015. We made 1, 536 observations of 68 bird species. The number of species and diversity significantly differed between the four localities. Mandalay Hill and Downtown Mandalay had the lowest number of species and diversity, whereas the University Campus and Paddy Fields had the highest. The highest number of observations was in Downtown Mandalay (1, 003 counts) and the lowest on Mandalay Hill (103). Nonmetric multidimensional scaling ordination techniques showed that the four habitat types had significantly different bird species composition. Our results indicate a large effect of urbanization on species diversity, species richness, and species composition of birds.